A Descriptive Socio-Legal Assessment on Gender and Human Rights - Kumar, Surender; Singh, Pawan Deep; Sarmah, Papori; Singh, Bijendra (Journal of Humanities and Social Sciences (JHASS), 2022)
Human rights violations of women and abuse against women are structured and underlying in India, introduced in socio-economic guidelines and laws that structure the family, neighborhood, climate, and state plans. Along these lines, it is an expanding worry in India and across the globe as the rising occurrence of infringements of women's human rights are on high. The purpose of this study is to investigate and examine the knowledge and mindfulness of human rights among women and its connection and association with the overall advancement of women in their day-to-day existence. Using a descriptive research method, both qualitative and quantitative data were gathered on women’s mindfulness and knowledge of various human rights available to them. The proximity of intense and thorough knowledge of women’s human rights was found to play the greatest role in the comprehensive socio-economic development of women. This study definitively answers the question regarding the correlation between proximity to women’s human rights mindfulness and fertile platform and ambiance for their fuller growth and development as human beings. Further investigations are expected to set up causal relations and foster a more full-bodied conceivable climate and social construction for the security and acknowledgement of women’s human rights.